Surrealism and architecture - Mical, Thomas, 1965- (Routledge, 2005)
This edited collection examines a long overlooked topic: the relationship of surrealist thought to architectural theory and practice. It offers a model for a new approach to historically rigorous analysis of interdisciplinary artistic practice.